Architecture in the Peruvian Real Estate Sector Based on Blockchain to Prevent Fraud - Quiroz, Andres Raul Dolorier (2024)
Within Peru's real estate realm, marked by discrepancies and opacity, this investigation explores the deployment of blockchain as a pioneering corrective, with Polkadot platform at its core. The study introduces a meticulous 6-stage smart contract protocol, encompassing the journey from initial recordal to blockchain-based contract consolidation. This methodology doesn't just forge an unalterable record; it also curtails intermediary dependence, thus bolstering transactional transparency and integrity. Initial findings endorse the viability and transformative potential of this approach, predicting a substantial evolution in Peru's property market. Moreover, in light of adapting to Peru's specific regulatory needs, the study underscores Polkadot's suitability over alternatives like Ethereum, marking it a superior choice in this national framework.